Array geometry calibration for underwater compact arrays. (February 2019) - Sun, Dajun; Ding, Jie; Zheng, Cuie; Huang, Weimin
Abstract: Array geometry calibration is necessary to ensure favorable performance of the array. Traditional techniques for array geometry calibration jointly estimate element positions, instrument delays, and constant sound speed (CSV) via nonlinear iterative method. The drawback is that the calibration results depends on the initial estimations. To improve the robustness and accuracy of the calibration results, a new array geometry calibration method for underwater compact arrays is proposed in this paper. In the new method, the position and instrument delay of each element are jointly estimated based on effective sound velocity (ESV) and time of flight (TOF) and the distances between elements are calculated subsequently, then the relative positions of elements are determined by trilateration. A compact pentagon array with a radius of 130 mm of a USBL positioning system is calibrated in an anechoic tank and a lake trial is conducted to test the performance of the results of array geometry calibration. As expected, the new method outperforms the traditional method, especially in regards to instrument delays and sound velocity estimations. The new method improves the array geometry horizontal precision from 0.6 mm to 0.12 mm and achieves a nearly onefold increase in USBL horizontal positioning accuracy compared to the traditional method.